Clinicopathological Study of Male Breast Malignancy in a Tertiary Care Hospital, Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2019)
Introduction: Male breast malignancy is a relatively rare condition among all the malignancies. It accounts for 0.2% of all malignant cases & less than 1% of all breast cancer.Methods and Materials: A retrospective observational study was done among the male patients with breast malignancy, admitted in Surgery ward in Shaheed Suhrawardy Medical College Hospital, Bangladesh from January 2014 to December, 2018.Results: Our series includes 09 patients. The mean age of the patient was 60 years. Most of the patients complaint breast lump with some degrees of skin colour changes. One has previous history of breast surgery (lumpectomy). Eight (8) patients went under simple mastectomy with axillary clearance after tissue diagnosis. One (1) patient got neo- adjuvant chemotherapy followed by surgery. Specimen was sent for histopathological & receptor study. Among them Infiltrating was ductal carcinoma was found in 07 cases, Sarcoma was in 01 (one) case & papillary carcinoma in 01 (one) case with 66.6 % positive oestrogen and progesterone receptor activity.Conclusion: Surgeons should be kept in mind that male breast malignancy is not uncommon and all male breast lumps should be evaluated properly before surgery.J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 48-51